Using Mayer’s Design Principles in Online Learning Modules: Implementation in a Student Centered Learning Environment - Yap, Wei Li; Neo, Mai (IEEE, 2013)
The use of technology in education is no longer something new in the universities. Lecturers may either develop learning modules to support the teaching and learning process or incorporate multimedia elements in the teaching materials. The use of multimedia elements in the teaching materials is able to attract students’ attention, achieve better retention rate and then improving students’ performances. The multimedia elements need to be used with proper planning and careful consideration in order to have the learning contents arranged in a more meaningful manner. One good approach is by following the Mayer’s Design Principles, which are Multimedia Principle, Spatial Contiguity Principle, Temporal Contiguity Principle, Coherence Principle, Modality Principle, Redundancy Principle, and Individual Differences Principle. On top of that, the interaction that is created during the learning process is also contributing into effective learning. This study looks into students’ perceptions on the independent online learning which is a student centered learning environment as well as the students’ performance in pretest/ posttest.